Properties of Transition Metals and Their Compounds at Extreme Conditions - Anzellini, Simone; Errandonea, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The characterization of the physical and chemical properties of transition metals and their compounds under extreme conditions of pressure and temperature has always attracted the interest of a wide scientific community. Their properties have numerous implications in fields ranging from solid-state physics, chemistry, and materials science to Earth and planetary science. The present Special Issue represents a good example of such a broad interest and shows some of the latest advancements in the investigation of transition metals under extreme conditions of pressure and temperature.